Fintech services market in Ukraine: current situation, problems and prospects - Venher, Yevgeniy; Nikiforov, Petro; Babuh, Ilona (My University, 2020)
In a globalized world there are radical changes in the construction of national financial systems, their organization and functioning under the influence of technological and financial innovations. Today, Fintech is the biggest driver of essentially revolutionary changes in financial systems at both the national and global levels. Ukraine does not stand aside from these processes, the state has some achievements, but according to experts, it lags behind developed markets, and therefore it is necessary to make up for lost. Most Fintech startups in Ukraine depend on equity in the absence of a functioning capital market. The infrastructure of electronic financial services remains imperfect. It is essential to change outdated legislation to promote a favorable business environment. The Ukrainian regulator should also promote the development of regulatory ‘sandboxes’ so that Fintech companies can use this tool. The classical banking system in ‘connections’ with the Fintech industry should be more active in digital multichannel banking, use artificial intelligence in its operations, do big data analytics based on artificial intelligence, use ‘cloud’ infrastructure. As for Ukrainian Fintech companies, their unique collective image looks like they are focused on the European market, have no investment from banks, focused on the B2B service model, are self-financed, top management has experience in traditional financial services, operates more than 3 years and still in development. Services are dominated by card payments and other types of payments. Competition in the market is insignificant due to the small number of Fintech companies. Ukrainian banks, in turn, do not have shares in the capital of third-party Fintech companies, have limited experience and understanding of the Fintech industry at the board level, but have specialists responsible for working with third-party software developers. There is no full-fledged interaction between banks and Fintech companies in Ukraine, although it is necessary for the further development of the financial services market, as currently market growth is less dependent on competition and more on raising awareness of the problems and technologies that can solve these problems.
Keywords: financial system; financial technologies; Fintech companies; Fintech market; Fintech sector; commercial banks; Ukrainian Fintech catalog; business models of financial services